Experimental Usutu virus infection in Eurasian blackbirds (Turdus merula) - Gianfilippo Agliani; Imke Visser; Eleanor M. Marshall; Giuseppe Giglia; Erwin de Bruin; Ruben Verstappen; Tjomme van Mastrigt; Felicity Chandler; Reina Sikkema; Henk van der Jeugd; Marion P. G. Koopmans; Andrea Gröne; et al. (npj Viruses)
Abstract Usutu virus (USUV) is a zoonotic arbovirus causing disease in wild birds and humans. Eurasian blackbirds (Turdus merula) are highly susceptible to infection, developing severe lesions with high mortality rates during outbreaks. The pathogenesis and clinical course of the acute disease in birds are not known. Therefore, six blackbirds were infected with two USUV lineages (Africa 3 and Europe 3). The blackbirds were monitored for clinical signs of disease and activity levels and were sampled for virus detection. All infected blackbirds showed severe disease after 4 to 7 days, with no significant differences between the lineages. Reaching a humane endpoint, the blackbirds were euthanized, and tissue samples were collected for histopathology and virology. At histopathology, lesions were seen in the main target organs with the associated presence of infectious virus and viral antigen. In conclusion, blackbirds can be infected experimentally with USUV and show similar disease as seen in natural infection.